Ethical principles of judges’ activity: Canadian experience - Hrubinko, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2024)
The article presents the results of a study of the main ethical principles of judges’ activities in foreign countries on the example of the Canadian judicial system. On the basis of regulations, case law, recommendations of the Judicial Council of Canada and scientific publications, the author examines the peculiarities of regulatory fixation and implementation of such ethical principles of judicial activity in Canada as the principles of judicial independence, good faith, equality, impartiality, non-partisanship, and necessity. The well-known ethical and legal principles of judicial activity in democratic states governed by the rule of law include the following requirements for judges: to exercise their judicial functions independently and without outside influence; to reject firmly any attempt to influence their decisions in any case before the court outside the due process of law; to promote and support measures and safeguards aimed at maintaining and strengthening the institutional and operational independence of the judiciary; to demonstrate and maintain high standards of judicial conduct.The author establishes that the legal system and case law of Canada pay special attention to such ethical principles of judges’ activities as the principles of judicial independence, good faith, equality, impartiality, non-partisanship, and necessity. Particular attention is paid to the regulation of a judge’s participation in public life, his or her involvement in political processes, his or her past work in business structures, corporate ethics of interaction between a judge and colleagues and other parties to a hearing, including lawyers, avoidance of conflicts of interest, and even requirements for ethical behavior of his or her relatives. Many of the rules and practical aspects of judges’ activities in Canada should be additionally taken into account in the Ukrainian judicial practice.